2020
DOI: 10.7717/peerj.8602
|View full text |Cite
|
Sign up to set email alerts
|

HER2 and BRAF mutation in colorectal cancer patients: a retrospective study in Eastern China

Abstract: Objective To investigate the frequency and prognostic role of the human epidermal growth factor receptor 2 gene (HER2) and BRAF V600E gene mutation in Chinese patients with colorectal cancer (CRC). Methods Clinicopathological and survival information from 480 patients with stage I–III CRC were reviewed and recorded. HER2 amplification was analyzed by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), BRAF V600E mutation was tested by IHC and Sanger sequencing. The relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
16
1
1
Order By: Relevance
“…HER2 scoring demonstrated high concordance rates between dual-color SISH and CISH methods as the results of the two techniques were almost identical showing 5 out of these 6 cases i.e 5/40 CRCs (12.5%) proved true for HER2 gene amplification. Our results were not far from studies of Valtorta et al, (2015) and Zhang et al, (2020) who reported that 5% and 5.63% of their CRC patients had HER2 amplification. Heppner et al, (2014) and Seo et al, (2014) stated that HER2 amplification ranged from 1.6% to 6.3%.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…HER2 scoring demonstrated high concordance rates between dual-color SISH and CISH methods as the results of the two techniques were almost identical showing 5 out of these 6 cases i.e 5/40 CRCs (12.5%) proved true for HER2 gene amplification. Our results were not far from studies of Valtorta et al, (2015) and Zhang et al, (2020) who reported that 5% and 5.63% of their CRC patients had HER2 amplification. Heppner et al, (2014) and Seo et al, (2014) stated that HER2 amplification ranged from 1.6% to 6.3%.…”
Section: Discussioncontrasting
confidence: 75%
“…An alternative is provided by the use of other in situ hybridization methods such as silver in situ hybridization (SISH) and chromogen in situ hybridization (CISH) which allows the use of an ordinary light microscope and has shown excellent correlation with results obtained using FISH (Abrahão-Machado et al, 2013). As the accurate assessment of HER2 gene amplification status in CRC appears to be particularly important for patients who might undertake this specific targeted therapy (Zhang et al, 2020).…”
Section: Differential Expression Of Her2 and Skp2 In Benign And Maligmentioning
confidence: 99%
“…Many recent reports have focused on RAS , BRAF (Raf murine sarcoma viral oncogene homolog B) and HER2 (human epidermal growth factor receptor 2 gene) mutations as predictive factors of mCRC patients who receive chemotherapy [ 98 , 99 ]. A study by Zheng investigated the frequency and prognostic role of HER2 and BRAF gene mutations in CRC patients.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A study by Zheng investigated the frequency and prognostic role of HER2 and BRAF gene mutations in CRC patients. The authors concluded that HER2 amplification significantly correlates with greater bowel wall invasion and a more advanced TNM stage, while HER2 amplification is an independent prognostic factor for worse disease-free survival [ 98 ]. Moreover, a statistically significant correlation for the RAS mutation and overall survival was also proved, whereas RAS mutation and liver metastasis were found to be independent factors for shorter overall survival of CRC patients in multivariate analysis [ 99 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…or single tumor-specific biomarkers (such as carcinoembryonic antigen CEA, carbohydrate antigen-CA199, etc.) [ 5 7 ]. To a certain extent, this can provide reference materials for evaluating the prognosis of tumors, however, due to the subjectivity in the collection of pathological data, the complexity and variability of tumor occurrence and development, only reference to clinicopathological data or a single tumor-specific marker cannot make a reliable prediction of tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%